2021
DOI: 10.1186/s12864-021-07425-4
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of root traits in wheat under different phosphorus levels using hydroponic culture

Abstract: Background Phosphorus (P) is an important in ensuring plant morphogenesis and grain quality, therefore an efficient root system is crucial for P-uptake. Identification of useful loci for root morphological and P uptake related traits at seedling stage is important for wheat breeding. The aims of this study were to evaluate phenotypic diversity of Yangmai 16/Zhongmai 895 derived doubled haploid (DH) population for root system architecture (RSA) and biomass related traits (BRT) in different P tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…MRL is an indication of root development potential for wheat yield improvement ( Li et al, 2021a ). Similar to previous studies ( Li et al, 2019 ; Yang et al, 2021 ), MRL was strongly correlated with other RSA-related traits except RD and RN in this study ( Table 2 ). By increasing the RA, RT, RV, and TRL, the contact area between roots and soil can be increased leading to the improvement of the efficiency of nutrient absorption for plants ( Ryser, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MRL is an indication of root development potential for wheat yield improvement ( Li et al, 2021a ). Similar to previous studies ( Li et al, 2019 ; Yang et al, 2021 ), MRL was strongly correlated with other RSA-related traits except RD and RN in this study ( Table 2 ). By increasing the RA, RT, RV, and TRL, the contact area between roots and soil can be increased leading to the improvement of the efficiency of nutrient absorption for plants ( Ryser, 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Besides, QRL.caas-7AL was mapped between AX-109966788 and AX-94819074 (731.90–742.24 Mb) on chromosome arm 7AL ( Yang et al, 2021 ), suggested that it might be allelic to QMrl.sicau-2SY-7A.2 (652.28–669.74 Mbp).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous research has been reported ( Su et al., 2009 ; Vijayalakshmi et al., 2010 ; Yang et al., 2016b ). The majority of chlorophyll content QTLs detected under CK, MP, and LP conditions are different, indicating that the chlorophyll regulation mechanism under low phosphorus conditions may differ from that under normal phosphorus conditions, and similar phenomena have been observed in previous research ( Yang et al., 2018 ; Yuan et al., 2020 ; Yang et al., 2021 ). Under multiple phosphorus conditions, six major QTLs Qchl.saw-2B.1 , Qchl.saw-3B.1 , Qchl.saw-4D.1 , Qchl.saw-4D.2 , Qchl.saw-5A.9 and Qchl.saw-6A.4 were detected ( Table 4 ).…”
Section: Discussionsupporting
confidence: 79%
“…To identify the localization of T. aestivum PSTOL1 orthologs with QTLs for morpho-physiological and biochemical traits under phosphorus starvation, QTLs and linked molecular markers were retrieved from previous publications [ 38 , 39 , 40 , 41 , 42 , 43 ], and co-localization was shown as described previously in [ 44 ]. To obtain the physical position, each marker sequence or marker name was BLAST against the grain gene database [ 45 ].…”
Section: Methodsmentioning
confidence: 99%